1991
DOI: 10.1016/s0005-2728(05)80316-0
|View full text |Cite
|
Sign up to set email alerts
|

Modified bacterial reaction centers. 4. The borohydride treatment reinvestigated: comparison with selective exchange experiments at binding sites BA,B and HA,B

Abstract: Pigments of borohydride-treated reaction centers of Rhodobacter sphaeroides R 26 and Rhodopseudomonas viridiswere analyzed by HPLC with polychromatie detection. In both species, pigment composition and contents were unchanged. Reaction centers from Rhodobacter sphaeroides R26 were prepared in which bacteriochlorophylls (B A B) and bacteriopheophytins (HA, n) were exchanged with their potential borohydride products reduced at C-3 t.[3-Hydroxyethyl]-BChl a exchanges selectively into the BA, B pockets, and 31-OH-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…To understand fully how these naturally occurring pigment–protein complexes harvest light so efficiently, it is necessary to employ spectroscopic tools that reveal directly the dynamics and efficiency of energy transfer and the nature of the excited energy states associated with the bound pigments. The spectroscopic studies are aided by the ability to make systematic alterations in the structures of the light-harvesting complexes, and then to examine how these changes manifest themselves in the spectroscopic observables, dynamics of energy transfer and efficiency of antenna function (Akahane et al 2004; Cammarata et al 1990; Chadwick et al 1987; Crielaard et al 1994; Croce et al 1999; Davidson and Cogdell 1981; Frank 1999; Fraser et al 1999; Morosinotto et al 2002; Olivera et al 1994; Olsen et al 1997; Plumley and Schmidt 1987; Remelli et al 1999; Struck and Scheer 1991; Struck et al 1992). …”
Section: Introductionmentioning
confidence: 99%
“…To understand fully how these naturally occurring pigment–protein complexes harvest light so efficiently, it is necessary to employ spectroscopic tools that reveal directly the dynamics and efficiency of energy transfer and the nature of the excited energy states associated with the bound pigments. The spectroscopic studies are aided by the ability to make systematic alterations in the structures of the light-harvesting complexes, and then to examine how these changes manifest themselves in the spectroscopic observables, dynamics of energy transfer and efficiency of antenna function (Akahane et al 2004; Cammarata et al 1990; Chadwick et al 1987; Crielaard et al 1994; Croce et al 1999; Davidson and Cogdell 1981; Frank 1999; Fraser et al 1999; Morosinotto et al 2002; Olivera et al 1994; Olsen et al 1997; Plumley and Schmidt 1987; Remelli et al 1999; Struck and Scheer 1991; Struck et al 1992). …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies performed on bacterial reaction centers (RCs) have shown that chemical modification of the RC chromophores by the exchange procedure [1, 2]or with borohydride (BH − 4 ) treatment [3–6]is a powerful way to investigate the contribution of particular pigments to the spectral and electron‐transfer properties of RCs. It is of great interest to apply similar methods to the isolated D1‐D2‐cytochrome (cyt) b ‐559 reaction center complex of photosystem II (PS II) [7], the spectroscopic and functional studies of which are seriously complicated by the fact that at least six chlorophyll and two pheophytin molecules contribute to the Q y absorption band of the complex in the range of 670–680 nm [8–12].…”
Section: Introductionmentioning
confidence: 99%
“…sphaeroides [43-45]. Although various chemical and enzymatic methods [46, 47] showed great success for exchanging the monomeric BChl and BPh pigments in RC complex, replacing BChl dimer in the core of RC complex has not been achieved [42, 48]. The non-exchangeable feature of the BChl dimer indicates its stronger interaction with protein than any other pigment and cofactor inside the RC complexes.…”
Section: Resultsmentioning
confidence: 99%